Jim Elliot : one great purpose - Benge, Janet, 1958-; Benge, Geoff, 1954- (Seattle, WA : YWAM Pub., 1999)
A profile of twentieth-century American missionary to the Auca Indians of Ecuador, who, along with four others, lost their lives trying to bring the Gospel to the people of Ecuador's jungle.
Includes bibliographical references (p. 189)
Keywords: Elliot, Jim, -- 1927-1956.; Elliot, Jim, -- 1927-1956 -- Juvenile literature; Missionaries -- Ecuador -- Biography -- Juvenile literature; Huao Indians -- Religious life -- Juvenile literature